Pembelajaran Kitab Taisirul Khalaq dalam Membentuk Akhlak Santri - Sutikno, Muhammad; Suhartono, Suhartono; Sholikah, Faridhotus (JUPIN (Jurnal Pendidikan Islam Nusantara), 2023)
Morality is a value that ensures the safety of humans from the torment of hellfire. The position of morality in human life holds a significant place, both as individuals and as a society and nation, as the rise and fall of a society depend on its morality. Morality itself is an inseparable part of human life and is able to distinguish humans from other creatures. In this study, a descriptive approach was used, where the collected data relied more on words. The writing method employed in this research is qualitative, and the aim is to describe the learning of the book Taisirul Khalaq in shaping morality. The methods used for data collection were observation, interviews, and documentation. The results of this study indicate that the learning of the book Taisirul Khalaq in shaping the morality of students at Madrasah Diniyah Pondok Pesantren Nurul Huda Sukaraja shows that students are able to understand and practice good moral values, including morality towards Allah, respect for parents, respect for teachers and students, respect for others (morality mahmudah and madzmumah), and can practice them in daily life.